COST-ANALYSIS OF REDUCING MORTALITY RATE FOR LBW BABIES AT FATMAWATI HOSPITAL'S NICU - Salim, Prasetya Rahman; Insani, Nadia Dwi; Sihaloho, Estro Dariatno (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2024)
Background: As a developing country that still struggles with infant mortality, Indonesia needs high-quality and efficient neonatal care. However, due to the complexity of neonatal care, the neonatal intensive care unit (NICU) still has a high cost, approximately USD 950 - 31,000, as the last line of care. Aims: This study analyzes the cost incurred due to service improvement at Fatmawati General Hospital. The cost analysis may serve as useful evidence for other hospitals with NICUs that seek to improve their service. Methods: We used cost analysis to examine pre-intervention costs in 2015 and post-intervention costs in 2021. Our data were gathered primarily in the NICU of Fatmawati General Hospital for three months in 2023. Results: The results showed an increase in total cost of IDR 1,898,040,489 (55%). The largest cost increase was personnel and supplies costs, which accounted for 83.8% of the cost increase. However, this cost increase was also followed by a significant decrease in mortality rates, from 128 deaths per 1,000 births to 17 deaths per 1,000 births. Conclusion: This study found a correlation between investment in service improvements and decreased infant mortality rates in the NICU of Fatmawati General Hospital. Although the 55% increase in total cost was associated with a significant decrease in infant mortality rates in the NICU of Fatmawati General Hospital, further studies are needed to determine the effectiveness of improvements in the NICU's services. Keywords: cost, Indonesia, LBW, NICU